Tomorrow, the world : the birth of U.S. global supremacy - Wertheim, Stephen (The Belknap Press of Harvard University Press, 2020)
"For most of its history, the United States avoided making political and military commitments that would entangle it in European-style power politics. Then, suddenly, it conceived a new role for itself as the world's armed superpower-and never looked back. In Tomorrow, the World, Stephen Wertheim traces America's transformation to the crucible of World War II, especially in the months prior to the attack on Pearl Harbor. As the Nazis conquered France, the architects of the nation's new foreign policy came to believe that the United States ought to achieve primacy in international affairs forevermore"--